Improvement of Accuracy Level of Automotive Front Fender Shield Assembly Using Process Failure Mode and Effect Analysis and Control Plan Techniques - Md Tohit, Khairul Nizam (2006)
Quality of products is the utmost important aspect that needs significant attention in order to fulfill customer’s requirements and satisfactions. Quality in the automotive industry can be defined as accuracy percentage of a part compared to the specifications that are fixed by the customer. Low accuracy percentage can contribute to various kinds of negative impacts for example, high rejection rate, increase warranty claim from customer, waste of time and productivity, tarnish company’s image and reputation and eventually will affect customer’s confidence. Therefore, preventive actions should be identified and implemented to ensure the negative effects that were caused from low quality parts would not happen. In this research, Process Failure Mode and Effect Analysis (PFMEA) and Control Plan techniques will be used as preventive tools to ensure products being produced will be of high quality and at the same time, meet customer’s specifications and requirements. Integration of both techniques will be used as reference to determine the potential failure modes, effects of failures to the process and recommended actions that need to be taken to reduce and eliminate the effects of failures. Each process involved in the manufacturing of products will be analysed by a specialist group consisting of several departments in the organisation, such as Engineering, Production and Product Development. Data analysis based on parts’ coordinate in X, Y and Z positions will be performed to determine the root caused of the failures. The data that has been analysed will be tabulated in a table with information, including differences between data collected compared to specifications and directions. Data in Prototype (P0 and P1) stage will be used to prove the effectiveness of the implementation of PFMEA and Control Plan techniques prior to and after both techniques have been applied in the product development process for Front Fender Shield Assembly Left Hand. The integration between PFMEA and Control Plan techniques and minimum target of 85% of accuracy level has been successfully achieved.